How to write for the world of work, seventh edition - Cunningham, Donald H.; Pearsall, Thomas E.; Smith, Elizabeth O. ([S.l.] : Thomson / Wadsworth, 2007)
A low cost alternative to books that blend Technical Communication and Business Communication, this new edition emphasizes the latest developments in these fields, including the importance of emerging technologies, global communications, and usability testing.